Knowledge, Attitude, and Practices Towards Standard Precautions on COVID-19 among Nursing Students at A Selected Private College - Diyanah Fadhilah Mahadi; Ashwinder Kaur Amarage Singh; Amarage Singh; Kavitha Sundram; Nurazlina Md Noor; YEE, BITLIAN (Talenta Publisher, 2022)
Since January 2021, higher education students are returning to their institutions to continue the banned education with serious application of preventive measures for COVID-19. It is essential to ensure all higher education students have adequate knowledge, favorable attitude, and good practice toward standard precautions for COVID-19. This study to assess the level of knowledge, attitude, and practices toward standard precautions on COVID-19 among nursing students at a private college. This study used a cross-sectional survey and a correlational study among 300 nursing students at a selected private nursing college. Data were collected using a self-administered questionnaire via Survey Monkey. Result of this study was most of the students have moderate knowledge (68.6%), good attitude (72.3%) and often (59%) practice Standard Precautions on COVID-19. For inferential analysis, all dependent variables did not have any relationship when the r-value is less than 1, but the attitude significantly differs significantly between knowledge (p=0.051) and practice (p=0.000). Moreover, the finding determined that the length of study gave influenced the knowledge (p=0.030) and practice (p=0.010) while education (p=0.018) and occupation (p=0.026) gave effect to the practice. Adequate information should be given to nursing students regarding the standard precautions of COVID-19.